An intimate resistance from the ruins of memory in the work of the poet Jorge Teillier (Anclajes, 2024)
The formation of an "intimate resistance" in the work of the Chilean poet Jorge Teillier (1935-1996) operates from the speaker’s nostalgic unfolding in the face of modern uprooting within a ruinous environment. This entails articulating the paradox between the speaker’s intimate everyday life experience and the sense of orphanhood caused by his current precarious existence, which encourages him to resignify the present and expand into the future. In this way, a pendular game of antagonisms arises in Tellier’s poetics: life and death, happiness and disappointment, rootedness and uprooting; a vital tendency of the speaker to disintegrate, counteracted with the intimate resistance from the ruins of his memory where he persists in his alterity and finitude.
Keywords: Modernity; Laric poetry; Nostalgia; Memory; Ruins